Profil Penguasaan Konsep Ikatan Kimia pada Siswa Kelas X SMA Negeri 4 Palangka Raya Tahun Ajaran 2017/2018 - Abdul Malik Sampurna; Mulawi Mulawi; I Made Sadiana (FKIP Universitas Palangka Raya, 2020)
The concept of chemical bonds is one of the subject matter of high school chemistry class X. This study aims to describe the mastery of the concept of chemical bonds in class X students of SMA Negeri 4 Palangka Raya in 2017/2018 Academic Year. This research is a descriptive qualitative research. The subjects of this study were 29 grade X students of SMA Negeri 4 Palangka Raya in 2017/2018 Academic Year who had received chemical bonding learning materials. The data used in this study are RPP documents obtained from the teacher concerned. Data on students' mastery of concepts was obtained through chemical bond description tests using 7 essay items covering 5 indicators. Supporting data using the results of interviews with students. Mastery of students' concepts in writing electron configurations and determining the electron valence of elements 94% with very high categories. Mastery of concepts illustrates the structure of Lewis 62% of the medium category. Mastery of concepts illustrates how an element to achieve stability of 74% in the high category. Mastery of concepts classifies the noble and non-gas elements 22% low category. Mastery of concepts explains the duplet rules and 20% octet rules in the low category. Mastery of the concept explains the process of forming 49% ion bonds in the medium category. Mastery of concepts illustrates Lewis's structure and determines the chemical formula of a single covalent bond compound of 51% of the moderate category. The mastery of the concept illustrates Lewis's structure and determines the chemical formula of 65% double covalent bonding compounds in the medium category. Mastery of concepts illustrates Lewis's structure and determines the chemical formula of 40% triple covalent bonding compounds in the low category. Mastery of the concept explains the process of forming coordination covalent bonds 29% in the low category. Mastery of the concept explains the process of forming metal bonds and explains the properties of metal-bound compounds respectively 31% and 45% in the low category.